Management Strategy to Improve the Image of Favorite Public Schools - Idrus, Roosmaria; Ahmad, Syarwani; Kesumawati, Nila (PPSDP International Journal of Education, 2023)
The purpose of this study is to examine the strategic management of building the image of favorite schools in senior high schools. The study employs qualitative methods. Data collection methods include interviews, documentation, observation, and a review of the literature. The descriptive qualitative analysis was used to analyze the data. According to the findings, the strategy for State Senior High Schools was to improve school quality, which included the quality of learning, the quality of school output, the participation of school members and the community, the quality of teachers, and the quality of school infrastructure. The challenge in implementing the strategy to improve the quality of learning that can always keep up with changes is the strategy to improve the image of favorite public schools. As a result, schools must continue to make efforts to increase teacher’s competency and capacity building activities through education and training, workshops, socialization, and training. Management strategy to build the image of a favorite high school that focuses on school output quality has a high public interest impact.